2012
DOI: 10.1055/s-0032-1312650
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Fasting Bioavailability and Pharmacokinetic Properties of 2 Formulations of Glucosamine Hydrochloride in Healthy Chinese Adult Male Volunteers

Abstract: Glucosamine (CAS 66-84-2) hydrochloride is an amino monosaccharide indicated for the treatment of arthrosis, especially osteoarthritis of the knee joint. This study was conducted to assess and compare the pharmacokinetic (PK) properties, bioavailability of a newly developed dispersible tablet formulation (test) of glucosamine hydrochloride with those of an established branded capsule formulation (reference) in healthy Chinese adult male volunteers.This single-dose, randomized, open-label, 2-period crossover st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The PK values of glucosamine from both sources were in consistent with those reported elsewhere. For example, Wu and co-authors reported a mean Cmax 944 ng/mL at 3.3 h, and mean AUC 0– ∞ , 3091 ng/mL/h, after 1500 mg glucosamine KCL dose was administrated by healthy subjects, with a mean half-life elimination of 1.5 h [ 17 ]. Using a glucosamine sulfate in solution dose, a mean Cmax of 1022 ng/mL was reached with a Tmax of 3.2 h, and mean value of AUC 0–4h and AUC 0– ∞ obtained were 4034 and 4194 ng/h/mL, respectively [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PK values of glucosamine from both sources were in consistent with those reported elsewhere. For example, Wu and co-authors reported a mean Cmax 944 ng/mL at 3.3 h, and mean AUC 0– ∞ , 3091 ng/mL/h, after 1500 mg glucosamine KCL dose was administrated by healthy subjects, with a mean half-life elimination of 1.5 h [ 17 ]. Using a glucosamine sulfate in solution dose, a mean Cmax of 1022 ng/mL was reached with a Tmax of 3.2 h, and mean value of AUC 0–4h and AUC 0– ∞ obtained were 4034 and 4194 ng/h/mL, respectively [ 18 ].…”
Section: Discussionmentioning
confidence: 99%